PENINGKATAN ANGGARAN MILITER CINA DAN IMPLIKASINYA TERHADAP KEAMANAN DI ASIA TIMUR - Adi Joko Purwanto (SPEKTRUM, 2010)
AbstractThe article is meant to know further China’s background in increasing its military expenditure through describing its armed forces’ defense policy especially in its military expenditure and by seeing how far the impact of China’s defense policy, especially in East Asian region, is. Based on the gathered data actually the increase of China’s military expenditure is a natural and realistic thing and it is not supposed to evoke a concern from other countries. This is because other countries could haveperformed what China is performing by, of course, measuring the countries’ ability.Key Words: Increase on military  expenditure, East Asian region, China’s economic growth,  China’s armed forces’ modernization, maritime territorial dispute and China- Japan relationship.